Qualitative Study of the Implementation of School Health Program in Junior High School 1 Teras and Junior High School 2 Andong - Putri Zahira, Aura; Umaroh, Ayu Khoirotul (P3M Universitas 'Aisyiyah Surakarta, 2024)
UKS is a school activity that is very important in school life, both for students, teachers, employees, and residents within the scope of the school. This study is a qualitative research with a case study approach that aims to find out the implementation of Trias UKS at SMP X Teras and SMP X Andong. Informants were selected using purposive sampling method. The results of the research conducted were that SMP X Teras and SMP X Andong carried out UKS programs, namely health education including counseling on PHBS, drugs, reproductive health, and TTD. Health services include screening, provision of TTD, and immunization and environmental development includes waste classification, bathroom cleanliness, healthy canteen development and non-smoking areas. The impact of the school's UKS program includes a safe and peaceful school environment, the creation of smooth teaching and learning activities for students. In the implementation of the UKS program, it is expected that schools can implement the UKS program according to the Technical Guidelines for the Implementation of Healthy Schools/Madrasahs in 2021, schools are expected to be able to allocate funds to implement the UKS program, and the need to increase school cooperation with related parties in the context of implementing the UKS program.